Factors Affecting Repurchase Intention on Tokopedia (Case Study in the Greater Jakarta Area) - Widjaja, Anthony Widjaja; Wijaya, Erric; Rofianto, Whony; Maju Simatupang, Batara (Dinasti Publisher, 2025)
The digital era is changing consumer behavior with the increasing use of the internet and social media that encourages the growth of e-commerce in Indonesia. This study analyzes the factors that affect the repurchase intention of Tokopedia users in the Greater Jakarta area, including Effort Expectancy, Perceived Usefulness, Information Quality, Perceived Risk, Social Influence, Trust, and Satisfaction. With a quantitative approach and SEM method (SmartPLS 4) on 170 respondents, the results showed that Trust, Satisfaction, Effort Expectancy, Perceived Usefulness, Information Quality, and Social Influence had a significant positive effect on repurchase intention, while Perceived Risk had a negative effect. These findings affirm the importance of improving service quality, transaction security, and Tokopedia's marketing strategy to strengthen customer loyalty.